Capacity building for conservation of the subterranean biodiversity of the Skadar/Shkodra Lake basin (Montenegro and Albania) - Magdalena Năpăruş-Aljančič; Miloš Pavićević; Leonid Merzlyakov; Tajda Turk; Philippe Theou; Denik Ulqini; Spase Shumka; Gregor Aljančič (Natura Sloveniae)
n/a